An Analysis of Expenditure Management Procedures at the Department of Food Crops and Horticulture - Audira Ayu Yulistia NH; Anissa Yuniar Larasati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Regional financial governance in Indonesia continues to face challenges in implementing structured and accountable expenditure procedures, especially within technical agencies. One such case is the West Java Provincial Office of Food Crops and Horticulture, where high operational demands and limited staff competencies often lead to procedural inconsistencies and weakened internal control systems. This study aims to evaluate the conformity of spending procedures with regulatory frameworks and to uncover key institutional obstacles impeding effective financial management. Employing a descriptive qualitative approach, data were gathered through structured interviews, direct observations, and document analysis, then interpreted using the Miles and Huberman interactive model. The results reveal critical procedural gaps including the absence of dedicated verification officers, overlapping financial roles, and inadequate standard operating procedures (SOPs). These factors collectively diminish internal control and undermine the credibility of financial reporting. The study concludes that organizational improvements, particularly in staff role separation, technical training, and SOP reform, are essential to strengthen accountability and transparency. The findings contribute to the theoretical understanding of internal control systems and provide practical recommendations for enhancing expenditure governance in regional public institutions.